Meta-analysis: The Effectiveness of Iot-Based Flipped Learning to Improve Students' Problem Solving Abilities - Muhammad Edy Nurtamam; Tomi Apra Santosa; Ilwandri Ilwandri; sanju aprilisia; Abdul Rahman; Yayat suharyat (Edumaspul: Jurnal Pendidikan, 2023)
This study aims to determine the effectiveness of IoT-based flipped learning to improve students' problem-solving skills. This type of research is meta-analysis research. The data sources in this study came from 11 national and international journals. Data sources were searched through Google Scholar, ScienceDirect, Wiley, and Eric. The data collection technique is direct observation through online databases. The inclusion criteria in this study are 1) data sources in the form of national and international journals published from 2019-2023; 2) Experimental or quasi-experimental type of research; 3) Research on flipped learning and solving skills. Research on flipped learning and student problem-solving skills and 4) Data sources in the form of journals or proceedings indexed by SINTA, DOAJ, and Scopus. Data analysis is quantitative descriptive analysis with the help of the JASP application. The results showed that the average effect size value (ES = 0.839) was high. This finding shows that the IoT-based flipped learning model can improve students' problem-solving skills. The flipped learning model helps students to be more creative and innovative in learning.